Analisis Formalisasi Struktur Organisasi Terhadap Efektivitas Kinerja Pemerintahan Pada Kabupaten Buleleng - Ahmad Muksin; Muhammad Rizki Dimas Setiawan; Muhammad Arief Naufal; Zeina Sekar Ayu Pramesti; Al- Hildayanti; Arkan A (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2023)
The purpose of this research analysis is to find out how the formalization of government organizational structures has an impact on organizational performance. In an organization, the organizational structure ensures that each member has equal responsibilities and that work will be divided equally. The ability to work effectively meeting the requirements and complying with all organizational rules is critical to an organization's success in achieving their goals. In terms of achieving each worker's work goals, a worker is considered to have high work effectiveness if they are able to achieve these goals.